Roles of perceived behavioral control and self‐efficacy to volunteer tourists' intended participation via theory of planned behavior - Lee, Seungwoo John; Lina Kim, Hyelin (The international journal of tourism research, 2018)
Volunteer tourism, as an alternative to mass tourism, has grown significantly since the 1970s, sparking a growing research interest in the subject. However, little research has been conducted about Asian volunteer tourists. The purpose of this study is to compare the strength of perceived behavioral control with self‐efficacy to predict volunteer tourists' intentions within the theory of planned behavior. Meta‐analysis is also used to examine the effect size of the independent variables derived from the theory of planned behavior. Study results indicate that self‐efficacy is a stronger predictor than perceived behavioral control in predicting volunteer tourists' future behavioral intentions.